Exploring Institutional Policies and Perspectives on Curriculum Internationalization and Global Citizenship Education: A Case Study at Universidad Antonio Nariño - Quevedo Padilla Laura Bibiana (Universidad Antonio Nariño, 2024)
This study employs a case study method to assess the implementation of Internationalization of the Curriculum (IoC) and Global Citizenship Education (GCED) within Universidad Antonio Nariño's Faculty of Education. This study explores institutional regulations, as well as educators' and coordinators' perceptions regarding the process of IoC and GCED. The research methodology includes document content analysis, Likert-scale surveys administered to 40 educators and 6 coordinators, and focus groups